Constraining primordial non-Gaussianity by combining photometric galaxy and 21 cm intensity mapping surveys - Mponeng Kopana; Sheean Jolicoeur; Roy Maartens (European Physical Journal C: Particles and Fields)
Abstract The fluctuations produced during cosmic inflation may exhibit non-Gaussian characteristics that are imprinted in the large-scale structure of the Universe. This non-Gaussian imprint is an ultra-large scale signal that can be detected using the power spectrum. We focus on the local-type non-Gaussianity $$f_NL$$ f NL and employ a multi-tracer analysis that combines different probes in order to mitigate cosmic variance and maximize the non-Gaussian signal. In our previous paper, we showed that combining spectroscopic galaxy surveys with 21 cm intensity mapping surveys in interferometer mode could lead to a $$\sim $$ ∼ 20–30% improvement in the precision on this non-Gaussian signal. Here we combine the same 21 cm experiments, including also single-dish surveys, with photometric galaxy surveys. The 21 cm single-dish surveys are based on MeerKAT and SKAO and the interferometric surveys are alike to HIRAX and PUMA. We implement foreground-avoidance filters and utilize models for the 21 cm thermal noise associated with single-dish and interferometer modes. The photometric galaxy surveys are similar to the DES and LSST. Our multi-tracer Fisher forecasts show a better precision for the combination of the photometric galaxy surveys and 21 cm interferometric surveys than with the 21 cm single-dish surveys – leading to at most an improvement of $$23%$$ 23 % in the former case and $$16%$$ 16 % in the latter case. Furthermore, we examine the impact of varying the foreground filter parameter, redshift range and sky area on the derived constraint. We find that the $$f_NL$$ f NL constraint is highly sensitive to both the redshift range and sky area. The foreground filter parameter shows negligible effect.